KEANEKARAGAMAN ARTHROPODA DAN KEPADATAN POPULASI IMAGO PENGGEREK BATANG PADI PUTIH Scirpophaga innotata Wlk. (LEPIDOPTERA : PYRALIDAE) PADA LINGKUNGANPERTANAMAN PADI YANG BERBEDA DIKABUPATEN PARIGI MOUTONG - Harman Hr.Komi,Moh Hibban Toana,Mohammad Yunus, Muhammad (AGROTEKBIS, 2015)
This study aims to determine the diversity of arthropods and population density imago white rice stem borer S. innotata in a different environment paddy crop in the district of Parigi Moutong. This study was conducted in two villages, village Lobu and village Olaya.This research was carried out for 3 months with observation interval one week, months December 2014 to February 2015. This study used a survey method and purposive sampling (selection of sites in a residential environment paddycrop and forest edges are attacked imago white rice stem borer S. innotata), The locations were divided into two rice crops Environment Environmental namely rice crops and the surrounding residential neighborhood on the outskirts of rice planting natural forests. Trapping techniques done in two ways, namely trapping insects in the day 'Pan Trap' (At 07.00 pm to 17.00 pm) and night 'Light Trap "(At 18:00 pm until 5:00 pm) while the population density imago white rice stem borers in two neighborhoods Different calculated based on the results of Arthropods in the can inside the trap. The results showed that the index Arthropod Biodiversity around the settlements amounted to 3,159 while the natural forest outskirt of 3192, this shows that environmental stability in the high category. High category indicates that the steady ecosystem stability and high productivity. Imago population density of white rice stem borer S.innotata around settlement was higher by 332 individuals compared to natural forest outskirt of 178 individuals.